Structure of Microbial Communities and Biological Activity in Tundra Soils of the Euro-Arctic Region (Rybachy Peninsula, Russia) - Maria V. Korneykova; Vladimir A. Myazin; Nadezhda V. Fokina; Alexandra A. Chaporgina; Dmitry A. Nikitin; Andrey V. Dolgikh (Microorganisms, 2023)
The relevance of the Arctic regions’ study is rapidly increasing due to the sensitive response of fragile ecosystems to climate change and anthropogenic pressure. The microbiome is an important component that determines the soils’ functioning and an indicator of changes occurring in ecosystems. Rybachy Peninsula is the northernmost part of the continental European Russia and is almost completely surrounded by Barents Sea water. For the first time, the microbial communities of the Entic Podzol, Albic Podzol, Rheic Histosol and Folic Histosol as well as anthropogenically disturbed soils (chemical pollution and human impact, growing crops) on the Rybachy Peninsula were characterized using plating and fluorescence microscopy methods, in parallel with the enzymatic activity of soils. The amount and structure of soil microbial biomass, such as the total biomass of fungi and prokaryote, the length and diameter of fungal and actinomycete mycelium, the proportion of spores and mycelium in the fungal biomass, the number of spores and prokaryotic cells, the proportion of small and large fungal spores and their morphology were determined. In the soils of the peninsula, the fungal biomass varied from 0.121 to 0.669 mg/g soil. The biomass of prokaryotes in soils ranged from 9.22 to 55.45 μg/g of soil. Fungi predominated, the proportion of which in the total microbial biomass varied from 78.5 to 97.7%. The number of culturable microfungi ranged from 0.53 to 13.93 × 103 CFU/g in the topsoil horizons, with a maximum in Entic Podzol and Albic Podzol soils and a minimum in anthropogenically disturbed soil. The number of culturable copiotrophic bacteria varied from 41.8 × 103 cells/g in a cryogenic spot to 5551.3 × 103 cells /g in anthropogenically disturbed soils. The number of culturable oligotrophic bacteria ranged from 77.9 to 12,059.6 × 103 cells/g. Changes in natural soils because of anthropogenic impact and a change in vegetation types have led to a change in the structure of the community of soil microorganisms. Investigated tundra soils had high enzymatic activity in native and anthropogenic conditions. The β-glucosidase and urease activity were comparable or even higher than in the soils of more southern natural zone, and the activity of dehydrogenase was 2–5 times lower. Thus, despite the subarctic climatic conditions, local soils have a significant biological activity upon which the productivity of ecosystems largely depends. The soils of the Rybachy Peninsula have a powerful enzyme pool due to the high adaptive potential of soil microorganisms to the extreme conditions of the Arctic, which allows them to perform their functions even under conditions of anthropogenic interference.